Comparison of Fractional Carbon Dioxide Laser Alone and in Combination with Subcision in Improving Atrophic Acne Scars - Mohammad Ali Nilforoushzadeh; Gita Faghihi; Fariba Jafari; Elaheh Haftbaradaran; Seyed Mohsen Hoseini; Nafiseh Mazaheri (مجله دانشکده پزشکی اصفهان, 2013)
Background: Acne is a very common skin disease. Scars are seen in 95% of patients with acne. Although numerous treatments have been recommended to cure acne scars, researchers are still searching for a single modality to treat the complication due to its variety in shape and depth. In other words, a combination of available methods is required to reach satisfactory results. We compared the effects of fractional carbon dioxide (CO2) laser alone and in combination with subcision.